2016
DOI: 10.1073/pnas.1524988113
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of transferred mutations is better predicted by the fitness of recipients than by their ecological or genetic relatedness

Abstract: The effect of a mutation depends on its interaction with the genetic background in which it is assessed. Studies in experimental systems have demonstrated that such interactions are common among beneficial mutations and often follow a pattern consistent with declining evolvability of more fit genotypes. However, these studies generally examine the consequences of interactions between a small number of focal mutations. It is not clear, therefore, that findings can be extrapolated to natural populations, where n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 66 publications
4
48
0
Order By: Relevance
“…In another study (Wang, et al 2016), several substitutions observed from an experimental evolution study of Escherichia coli were tested on a number of strains picked from the E. coli phylogeny. The authors asked whether the higher the ecological similarity between the E. coli strains used in the experimental evolution and tested now, the closer the growth effects of the substitutions in the two strains, but found only a marginally significant result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In another study (Wang, et al 2016), several substitutions observed from an experimental evolution study of Escherichia coli were tested on a number of strains picked from the E. coli phylogeny. The authors asked whether the higher the ecological similarity between the E. coli strains used in the experimental evolution and tested now, the closer the growth effects of the substitutions in the two strains, but found only a marginally significant result.…”
Section: Discussionmentioning
confidence: 99%
“…Diminishing returns epistasis is conventionally demonstrated by showing that the same mutation causes a smaller growth rate increase in a relatively fit strain than in a relatively unfit strain (MacLean, et al 2010;Chou, et al 2011;Khan, et al 2011;Kryazhimskiy, et al 2014;Wang, et al 2016). If the observed diminishing returns epistasis is genuine and general, it should also be testable by comparing the mean benefits of the mutation in two sets of strains that differ in mean growth rate (see Materials and Methods).…”
Section: Quantifying Diminishing Returns Epistasis By Comparing Mean mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, closely related strains can differ in the classification of genes that are essential for viability under a specific growth condition (39) . The same is true of mutations classified as beneficial in one strain background (including different mutations in the same gene, 40) , which can be neutral or deleterious in other backgrounds (e.g., [41][42][43][44] . Different strain backgrounds also may exhibit different mutation rates, thereby affecting the frequency with which genetic variation arises (45,46) .…”
Section: Introductionmentioning
confidence: 98%